EXAMINING TEACHERS’ PERFORMANCE: THE EFFECT OF WORK ETHOS, PERSONALITY COMPETENCE, ORGANIZATIONAL CULTURE, AND REWARDS - Sari Finishiawati, Happy Diyah; Mursito, Bambang; Aryati, Ida; Nugrahani, Dewi Shanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Teachers' performance serves as one of the most pivotal aspects in determining the success of the education and learning process. Work ethos, personality competence, organizational culture, and rewards are among the factors influencing teachers’ performance. The present study aimed to investigate the effect of work ethos, personality competence, organizational culture, and rewards on the teachers’ performance in SMP Batik Surakarta.This research method uses a quantitative descriptive research design with a population of 46 teachers of SMP Batik Surakarta. The sampling technique used was the census technique. The data were collected using a questionnaire and analyzed using multiple linear regression analysis, coefficient of determination test, t-test, and F-test.The result indicated that the work ethos, personality competence, organizational culture, and rewards positively and significantly affect teachers’ performance in SMP Batik Surakarta. These four variables were found to contribute 80% to teacher performance. work ethos, personality competence, organizational culture, rewards, teachers’ performance.